2003
DOI: 10.1159/000069898
|View full text |Cite
|
Sign up to set email alerts
|

Stroke in Parents Who Lost a Child: A Nationwide Follow-Up Study in Denmark

Abstract: The association between psychological stress and stroke remains uncertain. We therefore examined whether or not one of the most extreme psychological stressors, the death of a child, was associated with the risk of stroke in a nationwide population-based follow-up study. All 21,062 parents who lost a child in Denmark during 1980–1996 were compared with 293,745 parents who had not lost a child. The overall adjusted relative risk (RR) of stroke was 1.00 (95% CI = 0.83–1.20) among the exposed after up to 18 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 21 publications
0
37
1
Order By: Relevance
“…However, the study by Rostila et al . found a statistically significant overall risk only for women, whereas Li et al . found no increased risk for any of the sexes.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…However, the study by Rostila et al . found a statistically significant overall risk only for women, whereas Li et al . found no increased risk for any of the sexes.…”
Section: Resultsmentioning
confidence: 87%
“…We included six studies: five cohort studies and one case‐crossover study . All studies were conducted in Europe or the USA (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies even suggest that the death of a sibling is more disruptive and involves a more severe grief process than other familial deaths [11]. Accordingly, it has been shown that associations between sibling deaths and mortality among remaining siblings are comparable and, in some instances, stronger than other familial deaths [11], [14] including the loss of a child [15]. Moreover, the fact that findings on the duration of grief following familial deaths are unclear [16] stresses the importance of studying whether associations are discerned in shorter or longer-term perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that the death of a young child increases parental mortality from all causes,2 as well as the risk of depressive symptoms,10 certain types of cancer,11 myocardial infarction,12 poor self-rated health,13 diabetes14 and suicide 15. Yet, some analyses have found no increase in risk in parents with regard to general health status,16 cancer morbidity17 or stroke 18. Studies have also examined the duration of bereavement.…”
Section: Introductionmentioning
confidence: 99%